2015
DOI: 10.14260/jemds/2015/2524
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Chronic Obstructive Pulmonary Disease (Copd) Patients With Reference to Echocardiographic Findings

Abstract: BACKGROUNDChronic Obstructive Pulmonary Disease (COPD) is a common and preventable disease, which has great implication on global health. It is acknowledged by WHO as a commonest cause of death worldwide. The major morbidity of COPD is due to its impact on cardiac performance. Right ventricular dysfunction is common in patients with COPD. Echocardiogram is a very simple and convenient bedside investigation to detect cardiac function and structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…Similar incidences were found in some previous studies. [10][11][12] In this study it was observed that RA/RV dilatation, RVH, Cor pulmonale, PAH and LVDD were statistically significant (p<0.05) when compared with severity of COPD. Jatav et al4 analysed echocardiographic findings with disease severity, which showed that in mild category no case of RA/RV dilatation was present while in moderate, severe and very severe categories it was present in 27.27%, 40.90% and 63.33% of cases respectively.…”
Section: Methodsmentioning
confidence: 86%
“…Similar incidences were found in some previous studies. [10][11][12] In this study it was observed that RA/RV dilatation, RVH, Cor pulmonale, PAH and LVDD were statistically significant (p<0.05) when compared with severity of COPD. Jatav et al4 analysed echocardiographic findings with disease severity, which showed that in mild category no case of RA/RV dilatation was present while in moderate, severe and very severe categories it was present in 27.27%, 40.90% and 63.33% of cases respectively.…”
Section: Methodsmentioning
confidence: 86%
“…Similar incidences were found in some previous studies. 8,10 On correlating the echocardiographic signs of right atrium enlargement, right ventricle dilatation and pulmonary hypertension correlated significantly with the severity of the COPD (p<0.05). This means that the increase in incidence of the above ECHO findings, with increasing disease severity (decreasing FEV1) was statistically significant.…”
Section: Discussionmentioning
confidence: 96%
“…7,8 Patients between 40-70 years form the maximum number of male patients admitted, mainly because of the longer interval of tobacco exposure and continual respiratory tract infections, which would have negotiated their quality of life.…”
Section: Discussionmentioning
confidence: 99%